Terms of References of the Assembly of States Parties to The International Criminal Court - Abd Al Ghafoor Saleh Mohammed; Mahmoud Mohamed Ali Mahmoud (Usuli Faqih Research Centre PLT, 2024)
Non-Indexed Publication